Effect of human land-use and natural coverage on taxonomic and functional richness of mammals and birds at regional scale - Montero, Guillermo Leonardo Florez (2017)
The variation in species richness has been explained by two major hypotheses: 1) Energy and Water dynamics, which explains the latitudinal gradient of biodiversity; and 2) Habitat Heterogeneity hypothesis, which shows that structurally more complex environments provide more niches by adding species diversity. Nevertheless, small scale studies have been pointed out the importance of the relationship between the number of species and the internal structure of the habitat and its disturbances. Due to the extensive effect of human disturbances on the biosphere, a more complex view of the relationships between human-modified tropical landscapes and their effects on all dimensions of biological diversity is necessary to ensure the success of biodiversity conservation and the management of the ecosystems functions. In this work, we analyzed the effect of anthropic land-use and natural coverage on the species richness of birds and mammals and mammalian guilds in the state of São Paulo, Brazil. We focused on three phases: 1) Energy - Water 2) Natural Coverage as an approximation to environment heterogeneity and 3) Anthropic land-use as an approximation to the effect of human disturbances. Using the Maximum Likelihood approach to select models, we selected the best explanatory variables for species richness to perform models to test the three hypotheses proposed to explain the richness of each group, the individual effect of each variable was also analyzed. Our database presented a great bias product of an unequal sampling effort along the grid that was attenuated by the selection of the best-surveyed cells through a complementarity analysis. We found that the anthropic land-use is the best explanatory hypothesis for birds and mammals richness. For mammalian guilds richness the Energy + Water hypothesis occupies the second place contrasting with the results widely presented in the literature, and revealing the importance of factors associated with human impact at regional scale. It emphasizes the positive relationship between richness and native vegetation cover, Conservation Units and Reforestation, and the negative relationship with the agricultural land-use. That reveals the importance of designing management policies that involve the conservation of remnants of native vegetation, the maintenance and creation of protected areas, and the focus of reforestation efforts for a more complex Forest Transition promoting the landscape connectivity.